Social technology in gray water reuse in the state of Paraíba and applicability of law 10.033/2013 for its stability (Research, Society and Development, 2022)
One of the main characteristics of the Brazilian semi-arid region is climate variability and water scarcity. The insertion of social water technologies in semi-arid regions is a new paradigm for living with water scarcity. As a way to encourage better use of water resources in urban and rural areas, the state of Paraiba enacted Law 10,033 - State Policy for Capturing, Storage and Use of Rainwater. The objective of this work is to evaluate the effectiveness of Law 10.033 and propose the use of social technology for the reuse of greater from the Bioágua system in the state of Paraíba. To carry out this study, a deductive and investigative research methodology was used, with a bibliographic, exploratory and descriptive nature. This law also includes policies for the reuse of gray water. It is expected that more public policies in this sense will be implemented as a complementary measure for the effectiveness of the management of water resources in the State of Paraíba. With regard to the results obtained, it can be noted that after the implementation of the Law, the quality in the fulfillment of social water policies has improved significantly, mainly in Paraíba, considering that the area is located in conditions that are often precarious when we talk about availability of water. water resources. Concluding that the application and implementation of laws aimed at this issue are extremely necessary, it is no use having laws, it is necessary that these laws are actually put into practice.